Effects of tertiary amyl alcohol, 2-Phenoxyethanol, quinaldine and benzocaine on the mortality and rna: DNA ratio in catla fingerlings (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The efficacy of tertiary amyl alcohol (TAA), 2-Phenoxyethanol (2 PE), quinaldine and benzocaine was evaluated to determine their optimal dosages for rapid induction and recovery in the first experiment. The second experiment focused on the determination of effects of 2 PE, quinaldine and benzocaine with oxygen for 1, 3 and 6 h on the mortality, water quality and RNA:DNA ratio at 400 g L-1 in catla Catla catla fingerlings in a truck transport simulation. TAA at 1.5 mL L-1, 2 PE 200 ?L L-1, quinaldine (4%) 200 ?L L-1 and benzocaine 30 mg L-1 were found to be effective in inducing complete immobilization and recovery within 4 minutes. 2 PE and benzocaine treatments did not have any immediate mortality, while control and quinaldine treatment, respectively, resulted in 20 and 7% immediate mortality at 6 h. Similarly, 2 PE and benzocaine treatments did not result in any delayed mortality, however, control and quinaldine treatments, respectively, had nearly 7 and 2% delayed mortality observed 24 h after transport. Results of this study suggest that catla fingerlings can be transported at 400 g L-1 for 6 hours by using low dose 2 PE, benzocaine and quinaldine with no or little mortality.J. Asiat. Soc. Bangladesh, Sci. 40(1): 121-131, June 2014